2014
DOI: 10.4103/0253-7613.144922
|View full text |Cite
|
Sign up to set email alerts
|

The effect of progesterone on systemic inflammation and oxidative stress in the rat model of sepsis

Abstract: Objectives:To explore the protective effect of progesterone on inflammation and oxidative stress in a rat model of sepsis created by cecal ligation and puncture (CLP).Materials and Methods:Rats were randomly divided into 4 groups: Overiectomy group (OVX), sham operated (control), sepsis (CLP) group and progesterone-treated CLP group (CLP+ progesterone). The rats in CLP+ progesterone group received intraperitoneal progesterone (2 mg/kg). Cardiac blood samples were obtained for the measurement levels of interleu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 28 publications
3
27
0
Order By: Relevance
“…However, when progesterone was also administered, the TH + neurone density was not significantly different from the controls, nor from the MPTP‐treated mice. There is evidence regarding the beneficial effects of progesterone on inflammation . Hence, we next investigated the effect of progesterone treatment on pro‐inflammatory macrophages in the myenteric plexus.…”
Section: Resultsmentioning
confidence: 99%
“…However, when progesterone was also administered, the TH + neurone density was not significantly different from the controls, nor from the MPTP‐treated mice. There is evidence regarding the beneficial effects of progesterone on inflammation . Hence, we next investigated the effect of progesterone treatment on pro‐inflammatory macrophages in the myenteric plexus.…”
Section: Resultsmentioning
confidence: 99%
“…It is well-known that interleukin 6 plays an important role in diagnosis and prediction of mortality of patients with sepsis [18,19]. Most sepsis studies are based on serum interleukin 6 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Also, they reported that interleukin 6 levels in brain tissue are not significantly changed after 24 h. In the literature, TNF-alpha was commonly measured as a marker for sepsis associated encephalopathy in the brain tissue. The interleukin 6 levels were measured in serum [1,19,2124]. …”
Section: Discussionmentioning
confidence: 99%
“…[25] Other research indicated that there was an increase in kidney MPO values as well as MDA values in kidney and liver tissue, but there was no significant different in liver MPO level. [41] The effect of long-term use of dapagliflozin on glucose homeostasis and diabetic nephropathy has previously been investigated. Dapagliflozin has improved hyperglycemia and albuminuria, depending on the dose (0.1-1.0 mg/kg), and reduced macrophage infiltration, gene expression of inflammatory cytokines, and oxidative stress in diabetic mice.…”
Section: Discussionmentioning
confidence: 99%